Association of limited joint mobility in childhood and adolescent diabetes mellitus patients with HBA1C, microalbuminuria, and retinopathy at Tygerberg Hospital, Western Cape, South Africa - Sekgabo, Nightingale (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020